Rekonstrukcja i ocena reżimów nadzwyczajnych w państwie socjalistycznym (na przykładzie powstania węgierskiego 1956 r.) - Prokop, Krzysztof (PRAWO i WIĘŹ, 2026)
The article examines the mechanisms for introducing, operating, and legitimizing emergency regimes in the realities of a socialist state in the context of the Hungarian uprising of 1956. According to the author, emergency regimes in socialist states were fundamentally political, not legal. They served to maintain the communist party’s monopoly and monolithic power, even at the expense of its formally declared legality. The experience of the Hungarian uprising reveals a structural contradiction between the ideology of “socialist legality” and the practice of applying emergency measures. An analysis of the 1956 case allows the author to draw conclusions about the comprehensive nature of such regimes in socialist states, pointing to their exemplary form.